Mapping the Distribution of Mangrove in Malaysia Using Geographic Information System (GIS) - Harun, Noor Azlin; Nazirah Mohamad Abdullah,; Nurul Hazirah,; Nurmasitah Amran,; Nur Hidayah Nasir, (Enhanced Knowledge in Sciences and Technology, 2024)
Malaysia's mangrove forests provide critical ecological functions such as coastal protection, carbon sequestration, and breeding grounds for a variety of marine species. However, anthropogenic activities and climate change pose risks to these ecosystems. The purpose of this research is to map the distribution of mangrove forests in Peninsular Malaysia and to assess the availability of various mangrove tree species. Geographic Information Systems (GIS) technology will be utilised to combine data from diverse sources, including satellite photography, ground-truthing data, and current species distribution maps. This research will be useful for conservation efforts and long-term management of mangrove ecosystems in Peninsular Malaysia. Besides, it can also be used in the development of the policies and in the restoration and rehabilitation projects that aim to protect these ecosystems